About a boy oder :der tag der toten ente - Weitz, Chris (Madrid Universal Pictures Iberia, 2002)
A cynical, immature young man is taught how to act like a grown-up by a little boy.
Hugh Grant, Nicholas Hoult, Toni Collette
No recomendada para menores de 12 años
Idiomas : Inglés y alemán. Subt.: inglés y alemán
Keywords: Películas cinematográficas -- DVD